Giant keystone type III perforator flaps for dermatofibrosarcoma protuberans defect reconstruction. (December 2019) - Nedu, Maria Eliza; Matei, Ileana Rodica; Georgescu, Alexandru Valentin
Abstract: Introduction: Dermatofibrosarcoma protuberans (DFSP) is a relatively rare malignant tumor, with important local aggressiveness. Case report: We present a case of a 59-years-old man with a history of Psoriasis and viral hepatitis C presented in our department with a giant lesion on the posterior trunk, of 24/36 cm, with pus and local bleeding, causing important anemia. The tumor was excised, creating an elliptical defect of around 34 × 42 cm down to fascial level, which was covered by two lateral flaps – modified Keystone type III. Results: The flaps were completely viable and integrated with small dehiscence, which were assisted to heal secondarily. Conclusion: Our paper presents a reliable alternative to skin grafting for a very large defect on the posterior trunk, the modified type III keystone flap, to our knowledge, for the first time presented for such a wide defect and on adult.